The Correlation of Community Development (CD) Program and Image of Company PT. Perkebunan Nusantara V (PTPN-V) Recipients Help Education Sector at Pekanbaru - Anuar Rasyid; Fuad Muchlis (Institut Pertanian Bogor, 2014)
AbstractStudy aimed to (1) analyze the relationship between the Community Development (CD) program and image of PTPN V in the education sector beneficiaries in Pekanbaru; (2) analyze the factors inhibiting and supporting the Community Development (CD) of PTPN-V. The first study conducted using quantitative methods while the second study using qualitative methods. Results showed a strong correlation between Community Development (CD) program and image of PTPN V in the education sector beneficiaries in Pekanbaru. Furthermore, the factors inhibiting the Community Development (CD) program that funds the education sector is relatively limited and should be selected for the program beneficiaries. The factor supporting the education sector of Community Development (CD) program was a good cooperation between company and educational organizations beneficiary of education program of Community Development (CD).Keywords: community development, image of company